„Cień wielkiego miasta. Procesy urbanizacyjne w strefie Poznania - Małuszyńska, Ewa (Wydział Prawa i Administracji UAM, 1988)
Urbanization processes which take place in functional, ecological, socio-professional and socio-cultural planes play an increasingly important role not only in towns but also in areas situated outside towns. Those processes are of specific character in areas located in close vicinity to big agglomerations, since professional and cultural urbanization is not always accompanied here by the urbanization of functions. Around a town appears a distinct zone of the influx of people, mostly townspeople. It is a zone characterized by a poorer development of services in comparison with areas more distant from a town. The shortage of services is compensated to some extent by better communication facilities connecting such a zone with the agglomeration. A zone of that kind is called a "shadow" of a town. The range of Poznań "shadow" has been determined and characterized by the following indicators: the growth of population, migration balance, directions of migration, number of trade, catering and serivce institutions, libraries and movie-theatres. The study was conducted in selected zones around Poznań. The range of Poznań "shadow" is delimited by the borders of communes adjacent to the town or by the two closest rings (up to 10 km.). The third ring (10 - 15 km. from the town) is a transition zone. The study of spatial differentiation of urbanization processes is important for planning the development of the agglomeration and the areas adjacent to the town.
The „shadow" of a big town. Urbanization processes in Poznań area